Akurasi Pengkodean Diagnosis dan Prosedur Medis serta Implikasinya terhadap Klaim JKN di RSUD Pandan Arang - Anton Susanto; Galih Maheswari Candraningtyas; Agus Trijono (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The National Health Insurance (JKN) program requires accurate coding of diagnoses and medical procedures for claims submission under the INA-CBGs payment system. This study aims to analyze the accuracy of diagnosis and procedure coding and its impact on claim verification and payment status at Pandan Arang Regional Hospital, Boyolali. A descriptive qualitative method with a retrospective approach was applied to 100 randomly selected inpatient claim files from January to March 2023. Results showed that 18% of diagnosis codes and 1% of procedure codes were inaccurate, leading to pending claim statuses with a total unreimbursed amount of IDR 286,930,600. Common coding errors included incorrect code selection, misidentification of the principal diagnosis, and inappropriate use of multiple and combination codes. These inaccuracies caused delays in verification, disrupted hospital cash flow, and increased administrative workload. The findings highlight the urgent need for continuous training, regular coding audits, and strengthened collaboration between medical and coding teams to enhance coding quality and ensure the effectiveness of the JKN claim process.